Perilaku Pelaku Perjalanan Terhadap Kebijakan Konversi Moda Angkutan Mini-Bus Menjadi Bus Kota di Kota Bandung - Prasetyanto, Dwi; Rizki, Muhamad; Gardjito, Wiena Rustanti (Department of Civil Engineering, Diponegoro University, 2021)
Bandung City Government plans to improve their bus services which are expected to decline traffic congestion,reduce air pollution, and improve road safety. One of the efforts is to implement the conversion policy of minibus/paratransit to public bus. The purpose of this study is to analyze people's behavior related for theconversion policy above and their intentions to use it. For that purpose, the analysis performed with the datathat obtained by interviewing public transport users in Bandung City. The method used in this research isTheory of Planned Behavior. It is found that, the effect of evaluation outcomes, motivation to comply andperceived power proven to be significant on the behavioral intention to shift the use of public transportationfrom mini public buses to city buses. The contribution of evaluation outcomes influences the highest comparedto other factors, which is 32.36%, this shows that the evaluation of the performance of city bus services is themost dominant factor in shaping the behavioral intention to use city bus. Positive perception towards theconversion policy is in the high number, however, the intentions to shift to public transport should be supportedby ensuring high quality bus services.